Preparation method of environment-friendly degradable rubber material
Through three-stage rubber refining and secondary vulcanization treatment of natural rubber materials, the problems of poor resistance and poor processing stability at high temperatures are solved, and the high mechanical strength, wear resistance and comprehensive performance of rubber materials are improved, and it is suitable for a variety of high-performance applications.
Patent Information
- Application Number
- CN202411924759.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-11
AI Technical Summary
The existing natural rubber materials have poor resistance at high temperatures, are prone to vulcanization and frost spraying, and their processing stability and rheology performance are poor, making it difficult to meet the needs of high-performance applications.
The natural rubber material is treated with three-stage rubber refining and secondary vulcanization. By controlling the refining temperature and time, the feeding order of each component is controlled, so that each component is mixed evenly, and the processing fluidity is good, so as to avoid vulcanization and frost spraying.
The obtained rubber material has excellent mechanical strength, elasticity, wear resistance, insulation, acid and alkali resistance, aging resistance, high and low temperature resistance and water resistance, and is suitable for diving suits, tires, wires and cables and other fields.
Smart Images

Figure BDA0005208970010000141 
Figure BDA0005208970010000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber material preparation, and in particular relates to an environmentally friendly and degradable natural rubber foam material and a preparation method thereof. Background Art
[0002] Rubber is a highly elastic polymer material with reversible deformation, good physical and mechanical properties and chemical stability. It is widely used in national defense, aerospace, deep-sea equipment, automobiles, high-speed rail, construction, industry, medical and health care, and daily life, and its demand is increasing. The rubber materials known in the market are mainly natural rubber and synthetic rubber. Among them, natural rubber is a natural product extracted from rubber trees, while synthetic rubber is a chemical substance artificially synthesized from petroleum resources. Due to its unique crystallinity and excellent self-reinforcement effect, natural rubber has better physical and mechanical properties (such as high strength, good toughness, etc.) compared with synthetic rubber, and has better degradability and less impact on the environment, which is more suitable for the needs of green and sustainable development. However, natural rubber contains protein, and its water absorption will affect the insulation and high temperature resistance of natural rubber; at the same time, a large number of unsaturated double bonds make the medium resistance and aging resistance of natural rubber poor; its processing stability is poor, and it is easy to have the problem of poor rheological properties.
[0003] Natural rubber has no use value until it is cross-linked by vulcanization, and the vulcanization system (generally composed of vulcanizers, accelerators and activators) occupies a dominant position in the preparation process of natural rubber materials or products. The most widely used vulcanization system is the sulfur vulcanization system, in which sulfur is the main vulcanizing agent. The thioether bond is formed through the vulcanization reaction, which increases the strength, wear resistance and aging resistance of natural rubber. Its rubber products are easy to degrade under certain conditions, but its high temperature resistance is poor, the compression permanent deformation is large, and it is easy to have vulcanization reversion, frosting and other phenomena, which in turn affects the performance of natural rubber products and is not conducive to meeting various application requirements.
[0004] Accelerators are mainly used to shorten the vulcanization time, reduce the amount of sulfur, lower the vulcanization temperature, improve the processing performance and physical and mechanical properties of rubber, and increase the utilization rate of sulfur. Commonly used accelerators include thiazoles, xanthamides, thiurams, dithiocarbamates and xanthates. Thiazole accelerators have a fast vulcanization speed, and the vulcanized rubber has good aging resistance, but the scorch time is relatively short and it has a bitter taste; sulfonamide accelerators have a long scorch period and a fast vulcanization speed, but they have an aftereffect and are prone to produce nitrosamine carcinogens, which is not environmentally friendly; thiuram accelerators have a fast vulcanization speed, but a short scorch period and are prone to produce nitrosamine carcinogens, which is not environmentally friendly; dithiocarbamate accelerators have a fast vulcanization speed, are extremely prone to scorch and are prone to produce nitrosamine carcinogens, which is not environmentally friendly; xanthate accelerators are environmentally friendly accelerators, and their molecular structure does not contain nitrogen, so no nitrosamine carcinogens will be produced during the vulcanization process, but they have a fast vulcanization speed, a very short scorch period and poor thermal stability.
[0005] Invention patent CN202210465731.8 discloses a lightweight and degradable rubber composite material for shoes, which is composed of natural rubber 3L, nano-silica, cyclohexane oil 4006, stearic acid, zinc oxide, polyethylene glycol 4000, polyisobutylene, accelerator, sulfur, natural acid-base regulator and volume-increasing filler. It has a simple operation process, moderate sulfur rate, light specific gravity, easy degradation and mild odor; however, the filler in the rubber composite material is a natural plant, which contains more sugars and proteins, which makes its waterproof performance general, and affects its insulation and high temperature resistance, and is prone to vulcanization reversion and other phenomena. It is not suitable for use in fields with high performance requirements such as national defense, military industry, aerospace, and deep-sea equipment. Invention patent CN202010738333.X discloses a highly wear-resistant, high-rebound, and environmentally friendly rubber material, which uses a natural main rubber material, filler materials generated from agricultural waste, and additives without heavy metal components to reduce the proportion of petroleum synthetic rubber materials, reduce the environmental burden, and protect the environment; and then adjust the main rubber material and additives to make the obtained rubber material have the characteristics of high wear resistance, high rebound and high anti-slip; however, the polybutadiene rubber and styrene butadiene rubber in the main rubber material are both synthetic rubbers, and their raw materials are petroleum resources. The synthesis process pollutes the environment, is not environmentally friendly, and is not easy to degrade; and the insoluble sulfur system used in the rubber material has general dispersibility, and at the same time, the thermal stability is general at temperatures above 105°C, which results in general processing stability of the rubber material and poor rheology, which in turn affects the quality of the patented rubber material products. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing an environmentally friendly and degradable rubber material. The rubber material has a simple preparation process, stable processing performance, excellent mechanical strength and resilience, as well as excellent wear resistance, insulation, acid and alkali resistance, aging resistance, high and low temperature resistance and waterproofness, and can be applied to diving suits, tires, wires and cables and other fields.
[0007] In order to achieve the purpose of the present invention, the present invention provides a method for preparing an environmentally friendly and degradable rubber material, which specifically comprises the following steps:
[0008] S1. Put the natural rubber into an internal mixer for high temperature plasticization. After plasticization, the rubber material is left for 6-8 hours to obtain plasticized rubber, so that the natural rubber molecular chain is relaxed and the plasticity is uniform;
[0009] S2. The above-mentioned plasticized rubber is added to an internal mixer, and then reinforcing fillers, palm oil paste, antioxidants, and active agents are added in sequence. The first stage of plasticization is performed in the internal mixer at a temperature of ≤125°C for 30-60s to obtain the first stage of rubber mixing;
[0010] S3. When the temperature of the first stage of rubber mixing reaches 125±2°C, add the required 1 / 3 mass fraction of rubber softening oil, zinc oxide, foaming agent, vulcanizing agent, and accelerator in turn, and perform the second stage of plasticizing in an internal mixer at a temperature of ≤115°C for 120-200s to obtain the second stage of rubber mixing;
[0011] S4. When the temperature of the second stage of rubber mixing drops to 110±2°C, the remaining 2 / 3 mass fraction of rubber softening oil is added for the third stage of plasticizing. When the temperature of the third stage of plasticizing reaches 120±2°C, the third stage of rubber mixing is discharged from the internal mixer to obtain a rubber compound;
[0012] S5. The rubber obtained in step S4 is placed in an open mill to cool down. When the temperature drops to 80±2°C, the rubber is thinly passed, packaged, and parked;
[0013] S6. The parked rubber is placed in an open mill for heating, and then placed in an extruder for filtration and sheeting. The sheet is then placed in a flat vulcanizer for the first vulcanization and foaming at 140 ± 2 ° C;
[0014] S7. After cleaning and trimming the vulcanized and foamed rubber material, vulcanization is performed for the second time to obtain the desired environmentally friendly and degradable rubber material.
[0015] The invention adopts three-stage rubber mixing and secondary vulcanization to process natural rubber materials. By controlling the rubber mixing temperature and time and the adding order of the components of the rubber material, the components of the rubber material of the invention are mixed evenly, the processing fluidity is good, the performance of each component is stable during the vulcanization process, the vulcanization rate is good, the phenomena of auxiliary agent migration, rubber burning, sulfur blooming and the like will not occur, and the obtained rubber material has better comprehensive properties such as mechanical strength, resilience, high temperature resistance, aging resistance and the like.
[0016] Furthermore, the environmentally friendly and degradable rubber material is made of the following raw materials in parts by weight: 100 parts of natural rubber, 22-27 parts of palm oil paste, 90-125 parts of reinforcing filler, 7.5-8.4 parts of foaming agent, 32-40 parts of rubber softening oil, 2.5-3.6 parts of vulcanizing agent, 2.0-4.0 parts of accelerator, 3.2-3.6 parts of zinc oxide, 5-7 parts of activator and 1.2-1.8 parts of antioxidant.
[0017] Furthermore, the natural rubber is composed of No. 5 standard rubber and eucommia gum in a mass ratio of (7-10): 1. The present invention selects environmentally friendly and degradable No. 5 standard rubber and eucommia gum as the main base rubber materials for proportioning, so that the obtained rubber material is biodegradable under certain conditions, which meets the requirements of modern environmental protection and sustainable development; at the same time, the addition of eucommia gum improves the chemical corrosion resistance and aging resistance of the natural rubber of the present invention, and has better insulation; the selection of No. 5 standard rubber reduces the protein content in natural rubber, improves the waterproofness of the present invention, and ensures that the present invention has excellent tensile strength, high and low temperature resistance, aging resistance, etc.
[0018] Furthermore, the reinforcing filler is composed of the following raw materials in parts by mass: 52-60 parts of kaolin, 35-45 parts of calcium carbonate and 12-20 parts of carbon black. The kaolin is imported kaolin with a mesh size of 8000, and the calcium carbonate is nano-grade active calcium carbonate. The reinforcing filler of the present invention is combined with kaolin, calcium carbonate and carbon black in an appropriate proportion, which not only improves the strength and hardness of the present invention, but also reduces the amount of carbon black used and reduces the cost; and the reinforcing filler composition can be evenly dispersed in the rubber material, so that the present invention has good processing performance, improves the vulcanization efficiency, and improves the aging resistance, chemical corrosion resistance, tear resistance and high and low temperature resistance of the present invention.
[0019] Further, the foaming agent is a composite foaming agent, that is, it is composed of foaming agent AC, foaming agent OBSH and 5-aminotetrazole in a mass ratio of (2.6-3.0):1:0.3. The present invention uses foaming agent AC, foaming agent OBSH and 5-aminotetrazole in an appropriate proportion for compounding, so that the foaming agent component is not easy to agglomerate, can be evenly dispersed in the rubber material, and has a low decomposition temperature. It can be uniformly foamed during the 140°C vulcanization process of the present invention, has a high foaming ratio, and the obtained closed-cell bubbles have a small pore size and uniform pores. At the same time, the foaming agent combination is an environmentally friendly foaming agent, and ensures that the present invention has excellent comprehensive performance.
[0020] Further, the vulcanizing agent is insoluble sulfur or sulfur-HEA. Preferably, the vulcanizing agent is homemade sulfur-HEA.
[0021] Furthermore, the preparation method of sulfur-HEA is as follows: sulfur and hydroxyethyl acrylate (HEA) in a molar ratio of (2.2-2.6):1 are placed in a reactor, heated to 160-180° C. in a nitrogen environment, stirred for reaction for 2-4 hours, the product is taken out and quenched, and then placed in a 60-80° C. oven for 2-3 hours to obtain sulfur-HEA.
[0022] The self-made sulfur-HEA of the invention adopts HEA to modify sulfur, that is, sulfur reacts with hydroxyethyl acrylate to obtain an organic sulfur-containing compound. The sulfur-HEA is not only lipophilic, but also easily dissolved in the rubber compound, thereby ensuring that sulfur does not bloom, and also improves the water resistance and processing thermal stability of the invention, and solves the problem that the existing insoluble sulfur is easily decomposed into sulfur at above 105° C.; at the same time, due to the introduction of HEA, the bonding force between the components such as reinforcing fillers and zinc oxide is improved, so that the invention has better mechanical strength, resilience, wear resistance, high temperature resistance and chemical corrosion resistance.
[0023] Furthermore, the accelerator is a xanthate accelerator containing benzothiazole, and the preparation method of the xanthate accelerator containing benzothiazole specifically comprises the following steps:
[0024] P1. Dopamine hydrochloride was dissolved in a Tris buffer with a pH value of 8.5 and ultrasonicated for 30 minutes, and then sodium isobutyl xanthate was added and ultrasonicated for 10 minutes, and then stirred at room temperature for 3-5 hours to obtain pretreated isobutyl xanthate;
[0025] P2. Dissolve 2-mercaptobenzothiazole in anhydrous ethanol, then add the above-mentioned pretreated isobutyl xanthate, stir and react at 60-80°C for 3-6 hours. After the reaction is completed, filter, dry and crush to obtain the desired benzothiazole-containing xanthate accelerator.
[0026] Furthermore, the amount of dopamine hydrochloride added is 6-9% of the mass of the sodium isobutyl xanthate;
[0027] The added amount of the 2-mercaptobenzothiazole is 20-30% of the mass of the sodium isobutyl xanthate.
[0028] Sodium isobutyl xanthate is a xanthate accelerator, and its molecular structure does not contain primary amine groups. Therefore, no nitrosamine carcinogens are produced during the vulcanization process, and it is an environmentally friendly accelerator. However, the vulcanization speed of the sodium isobutyl xanthate is very fast, which is very easy to cause scorching, and the thermal stability is poor, so it is only suitable for low-temperature vulcanization. The present invention pre-treats the sodium isobutyl xanthate by reacting it with dopamine hydrochloride at a pH value of 8.5 to obtain an isobutyl xanthate containing a lipophilic group (i.e., pre-treated isobutyl xanthate), and then 2-mercaptobenzothiazole is added to react to obtain the obtained product. The xanthate accelerator containing benzothiazole is used in conjunction with the vulcanizing agent of the present invention, which not only makes the present invention have a lower vulcanization temperature and a higher vulcanization efficiency, but also improves the processing thermal stability of the present invention, prolongs the scorching time, and makes it vulcanize at about 140°C, and still ensures that the present invention has better mechanical strength and high elasticity; at the same time, it also improves the water resistance, anti-vulcanization reversion performance, chemical corrosion resistance and aging resistance of the present invention.
[0029] Furthermore, the active agent is composed of oleylamine and zinc stearate in a mass ratio of 2:1. The active agent is prepared by mixing oleylamine and zinc stearate, which improves the vulcanization reaction speed and efficiency of the present invention, reduces the vulcanization temperature and time, and improves the mechanical strength and resilience of the rubber material.
[0030] Furthermore, the antioxidant is any one of antioxidant MB (2-mercaptobenzimidazole), antioxidant MMB (2-mercaptomethylbenzimidazole), antioxidant SP (styrenated phenol), antioxidant ZMMBI (2-mercapto-4 (or 5)-methylbenzimidazole zinc), and antioxidant NAPMA (N-(4-anilinophenyl)phenylformamide).
[0031] The present invention has achieved the following beneficial effects:
[0032] 1. The rubber material of the present invention is to firstly subject the natural rubber composed of No. 5 standard rubber and eucommia gum to high-temperature plasticization to make the rubber molecular chain relaxed and plastic, then control the order of adding the components of the rubber material, adopt three-stage rubber mixing (control the additives added in different rubber mixing stages, the rubber mixing temperature and the rubber mixing time) and secondary vulcanization to treat the natural rubber material, so that the components are evenly dispersed and the viscosity of the rubber material is moderate, so as to achieve stable processing performance and good rheological properties, and not prone to vulcanization reversion, frosting and the like. The obtained rubber material or product has excellent mechanical strength and resilience, and also has excellent wear resistance, insulation, acid and alkali resistance, aging resistance, high and low temperature resistance and waterproofness, and can be applied to diving suits, tires, wires and cables and other fields; the raw materials of the rubber material used in the present invention are environmentally friendly and degradable, which improves the degradability of rubber products and greatly reduces the impact of rubber waste on the environment.
[0033] 2. The vulcanization system of the present invention is composed of insoluble sulfur or sulfur-HEA, a xanthate accelerator containing benzothiazole, zinc oxide and an activator. Under the action of the xanthate accelerator containing benzothiazole, the sulfur vulcanization system has a lower vulcanization temperature, better vulcanization speed and efficiency, and improves the thermal stability of the vulcanization system. At the same time, no frosting or vulcanization reversion will occur during the vulcanization process, thereby making the rubber material obtained after vulcanization and cross-linking have better mechanical strength, high elasticity, wear resistance, insulation, acid and alkali resistance, aging resistance, high and low temperature resistance and waterproofness.
[0034] 3. The raw materials used in the present invention are non-toxic, environmentally friendly and degradable. The rubber material has stable structural performance, is recyclable or biodegradable, and is an environmentally friendly material that meets national environmental protection requirements.
[0035] 4. The raw materials of the rubber material of the present invention are easily available, the preparation process is simple and easy to operate, it has excellent processing performance, high comprehensive performance and low production cost, and can be applied to national defense and military industry, aerospace, deep-sea equipment, automobiles, high-speed rail, construction, industry, medical care and other fields. It has a wide range of applications and is suitable for large-scale promotion. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The environmentally friendly and degradable rubber material and the preparation method thereof of the present invention are described below in conjunction with specific embodiments.
[0038] Example 1
[0039] The method for preparing the environmentally friendly degradable rubber material of this embodiment 1 specifically comprises the following steps, measured by weight:
[0040] S1. 100 parts of natural rubber were put into an internal mixer (150L) for high-temperature plasticization. The plasticization temperature was 145°C and the plasticization time was 10 min. The plasticized rubber was left for 8 h to obtain plasticized rubber.
[0041] S2. Add the above-mentioned plasticized rubber into an internal mixer, and then add 125 parts of reinforcing filler, 22 parts of palm oil paste, 1.8 parts of antioxidant, and 7.0 parts of activator in sequence, and perform the first stage of plasticizing in the internal mixer at a temperature of 125°C for 45 seconds to obtain the first stage of rubber.
[0042] S3. Keep the temperature of the first stage of rubber mixing at 125°C, add 13 parts of rubber softening oil, 3.2 parts of zinc oxide, 7.5 parts of foaming agent, 3.6 parts of vulcanizing agent, and 4.0 parts of accelerator in sequence, and carry out the second stage of plasticizing in an internal mixer, and plasticize at a temperature of 115°C for 160s to obtain the second stage of rubber mixing.
[0043] S4. When the temperature of the second stage of rubber mixing drops to 110°C, the remaining 27 parts of rubber softening oil are added to carry out the third stage of plasticizing. When the temperature of the third stage of plasticizing reaches 120°C, the third stage of rubber mixing is discharged from the internal mixer to obtain a rubber compound.
[0044] S5. Put the rubber obtained in step S4 into a 24-inch open mill to cool down. When the temperature drops to 80°C, thin the rubber, pack it, and park it.
[0045] S6. Put the parked rubber into an open mill for heating, and then put it into a 250mm extruder for filtering and sheeting. Then put the sheet into a 2000-ton flat plate vulcanizer and keep it at 140°C for 15 minutes for the first vulcanization and foaming.
[0046] S7. After cleaning and trimming the vulcanized and foamed rubber material, continue to maintain it at 140°C for 8 minutes in a 2000-ton flat plate vulcanizer for a second vulcanization to obtain the desired environmentally friendly and degradable rubber material.
[0047] The above-mentioned natural rubber is composed of No. 5 standard rubber and eucommia gum in a mass ratio of 8:1, wherein No. 5 standard rubber is selected from Wuchang, Vietnam; and eucommia gum (natural eucommia gum) is selected from Shaanxi Jingfei Biotechnology.
[0048] The raw material composition of the reinforcing filler is as follows, by weight: 60 parts of kaolin, 45 parts of calcium carbonate and 20 parts of carbon black, wherein the kaolin is imported calcined kaolin Glomax LL with a particle size of 8000 mesh; the calcium carbonate is nano-activated calcium carbonate LP500; and the carbon black is selected from GAZPROM's carbon black N990.
[0049] The above-mentioned palm oil paste is selected from the palm oil paste BF160 of Qingdao Fluoro New Materials.
[0050] The above antioxidant is antioxidant MB, which is selected from Weilin New Materials.
[0051] The active agent is composed of oleylamine and zinc stearate in a mass ratio of 2:1.
[0052] The rubber softening oil is selected from NA-80 of Total.
[0053] The zinc oxide is nano-grade zinc oxide with fine spherical particles, which is selected from Longyuan Chemical.
[0054] The foaming agent is composed of foaming agent AC (azodicarbonamide), foaming agent OBSH (4,4'-oxybisbenzenesulfonylhydrazide, selected from OBSH-75 of LANXESS, Germany) and 5-aminotetrazole in a mass ratio of 3:1:0.3.
[0055] The above-mentioned vulcanizing agent is insoluble sulfur, which is selected from Weilin New Materials.
[0056] The above-mentioned accelerator is a xanthate accelerator containing benzothiazole, and its preparation method is as follows:
[0057] P1. 82 g of dopamine hydrochloride (selected from Guangzhou Shenglong Bio) was dissolved in 2 L of Tris buffer (i.e., a concentration of 1.12 g / L tris(hydroxymethyl)aminomethane solution) with a pH value of 8.5 and ultrasonicated for 30 min, and then 1 kg of sodium isobutyl xanthate was added and ultrasonicated for 10 min, and then stirred at room temperature for 4 h to obtain pretreated isobutyl xanthate;
[0058] P2. Dissolve 220g of 2-mercaptobenzothiazole in 500mL of anhydrous ethanol, then add the above-mentioned pretreated isobutyl xanthate, stir and react at 70°C for 5h. After the reaction is completed, filter, dry and crush to obtain the desired xanthate accelerator containing benzothiazole.
[0059] Example 2
[0060] The preparation method of the environmentally friendly degradable rubber material of Example 2 is the same as that of Example 1 in terms of parts by weight, and specific reference is made to Example 1. However, compared with Example 1, the differences of Example 2 are as follows:
[0061] The raw materials of the environmentally friendly and degradable rubber material of this embodiment are in parts by weight: 100 parts of natural rubber, 27 parts of palm oil paste (BF160), 99 parts of reinforcing filler, 8.2 parts of foaming agent, 32 parts of rubber softening oil NA-80 (wherein, 11 parts of rubber softening oil NA-80 are added in the second rubber mixing process and 21 parts of rubber softening oil NA-80 are added in the third rubber mixing process), 2.5 parts of vulcanizing agent, 2.5 parts of accelerator, 3.6 parts of zinc oxide (Longyuan Chemical), 5.2 parts of activator (oleylamine and zinc stearate in a mass ratio of 2:1) and 1.2 parts of antioxidant ZMMBI (Weilin New Materials).
[0062] The above-mentioned natural rubber is composed of No. 5 standard rubber (Vuchang, Vietnam) and Eucommia ulmoides gum (Jingfei Biological) in a mass ratio of 7:1.
[0063] The raw material composition of the reinforcing filler is as follows, by weight: 52 parts of kaolin GlomaxLL, 35 parts of calcium carbonate LP500 and 12 parts of carbon black N990.
[0064] The foaming agent is composed of foaming agent AC, foaming agent OBSH (OBSH-75 from LANXESS, Germany) and 5-aminotetrazole in a mass ratio of 2.6:1:0.3.
[0065] The above-mentioned vulcanizing agent is homemade sulfur-HEA, and its preparation method is: sulfur and hydroxyethyl acrylate (HEA) with a molar ratio of 5:2 (or a mass ratio of 160:232) are placed in a reactor, heated to 170°C in a nitrogen environment, stirred for reaction for 4 hours, the product is taken out and quenched, and then placed in a 70°C oven for 3 hours to obtain sulfur-HEA.
[0066] The above-mentioned accelerator is a xanthate accelerator containing benzothiazole. Its preparation method and raw materials are the same as those in Example 1. Please refer to Example 1 for details.
[0067] Example 3
[0068] The preparation method of the environmentally friendly degradable rubber material of Example 3 is the same as that of Example 1 in terms of weight, and specific reference is made to Example 1. However, compared with Example 1, the differences of Example 3 are as follows:
[0069] The raw materials of the environmentally friendly and degradable rubber material of this embodiment are in parts by weight: 100 parts of natural rubber, 23 parts of palm oil paste (BF160), 120 parts of reinforcing filler, 8.4 parts of foaming agent, 38 parts of rubber softening oil NA-80 (wherein, 13 parts of rubber softening oil NA-80 are added in the second rubber mixing process and 25 parts of rubber softening oil NA-80 are added in the third rubber mixing process), 3.2 parts of vulcanizing agent, 3.5 parts of accelerator, 3.5 parts of zinc oxide (Longyuan Chemical), 6.2 parts of activator (oleylamine and zinc stearate in a mass ratio of 2:1) and 1.6 parts of antioxidant ZMMBI (Weilin New Materials).
[0070] The above-mentioned natural rubber is composed of No. 5 standard rubber (Vuchang, Vietnam) and Eucommia ulmoides gum (Jingfei Biological) in a mass ratio of 10:1.
[0071] The raw material composition of the reinforcing filler is as follows, by weight: 60 parts of kaolin GlomaxLL, 42 parts of calcium carbonate LP500 and 18 parts of carbon black N990.
[0072] The foaming agent is composed of foaming agent AC, foaming agent OBSH (OBSH-75 from LANXESS, Germany) and 5-aminotetrazole in a mass ratio of 2.8:1:0.3.
[0073] The preparation methods and raw materials of the above-mentioned vulcanizing agent and accelerator are the same as those in Example 2, and specific reference is made to Example 2.
[0074] Example 4
[0075] The preparation method of the environmentally friendly degradable rubber material of Example 4 is the same as that of Example 3 in terms of parts by weight, and specific reference is made to Example 3. However, compared with Example 3, the differences of Example 4 are as follows:
[0076] The raw materials of the environmentally friendly and degradable rubber material of this embodiment are in parts by weight: 100 parts of natural rubber, 25 parts of palm oil paste (BF160), 112 parts of reinforcing filler, 8.0 parts of foaming agent, 36 parts of rubber softening oil NA-80 (wherein, 12 parts of rubber softening oil NA-80 are added in the second rubber mixing process and 24 parts of rubber softening oil NA-80 are added in the third rubber mixing process), 3.0 parts of vulcanizing agent, 3.0 parts of accelerator, 3.5 parts of zinc oxide (Longyuan Chemical), 6.0 parts of activator (oleylamine and zinc stearate in a mass ratio of 2:1) and 1.5 parts of antioxidant ZMMBI (Weilin New Materials).
[0077] The above-mentioned natural rubber is composed of No. 5 standard rubber (Vuchang, Vietnam) and Eucommia ulmoides gum (Jingfei Biological) in a mass ratio of 9:1.
[0078] The raw material composition of the reinforcing filler is 57 parts of kaolin GlomaxLL, 40 parts of calcium carbonate LP500 and 15 parts of carbon black N990 in parts by mass.
[0079] The preparation methods and raw materials of the above-mentioned foaming agent, vulcanizing agent and accelerator are the same as those in Example 3, and specific reference is made to Example 1.
[0080] Comparative Example 1
[0081] The components of the environmentally friendly and degradable rubber material of this comparative example are the same as those in Example 4, and specific reference is made to Example 4. The difference is that the preparation method of the environmentally friendly and degradable rubber material of this comparative example 1 is:
[0082] S1. The natural rubber was placed in an internal mixer (150L) and plasticized at 145°C for 10 min. The plasticized rubber was left for 8 h to obtain a plasticized rubber;
[0083] S2. The plasticized rubber is added to an internal mixer, and then reinforcing fillers, palm oil paste, antioxidants, activators, zinc oxide and rubber softening oil are added in sequence, and the first stage of plasticization is performed in the internal mixer at a temperature of 125 ° C for 45 seconds to obtain the first stage of rubber mixing;
[0084] S3. Keep the temperature of the first stage of rubber mixing at 125°C, add the foaming agent, vulcanizing agent and accelerator in sequence, and carry out the second stage of plasticizing in the internal mixer, and plasticize for 160s at a temperature of 115°C to obtain the second stage of rubber mixing.
[0085] S4. When the second stage plasticizing temperature reaches 120 ° C, the second stage of the rubber is discharged from the internal mixer to obtain the rubber, and then the rubber is placed in a 24-inch open mill to cool down. When the temperature drops to 80 ° C, the rubber is thinly passed, packaged, and parked;
[0086] S5. Put the parked rubber into an open mill for heating, and then put it into a 250mm extruder for filtering and sheeting. Then put the sheet into a 2000-ton flat plate vulcanizer and keep it at 140°C for 15 minutes for the first vulcanization and foaming.
[0087] S6. After cleaning and trimming the vulcanized and foamed rubber material, continue to maintain it at 140°C for 8 minutes in a 2000-ton flat plate vulcanizer for a second vulcanization to obtain the desired environmentally friendly and degradable rubber material.
[0088] Comparative Example 2
[0089] The components of the environmentally friendly and degradable rubber material in this comparative example are the same as those in Example 4, and specific reference is made to Example 4. The difference is that the natural rubber in this comparative example 2 is No. 5 standard rubber.
[0090] Comparative Example 3
[0091] The components of the environmentally friendly and degradable rubber material in this comparative example are the same as those in Example 4, and specific reference is made to Example 4. The difference is that the foaming agent in this comparative example 3 is composed of foaming agent AC and foaming agent OBSH (OBSH-75 from LANXESS, Germany) in a mass ratio of 2.8:1.
[0092] Comparative Example 4
[0093] The components of the environmentally friendly and degradable rubber material of this comparative example are the same as those in Example 4, and specific reference is made to Example 4. The difference is that the vulcanizing agent of this comparative example 4 is sulfur-EHA, and its preparation method is as follows: sulfur and isooctyl acrylate (EHA) with a molar ratio of 2.5:1 are placed in a reactor, heated to 170°C in a nitrogen environment, stirred for reaction for 4 hours, the product is taken out and quenched, and then placed in a 70°C oven for 3 hours to obtain sulfur-EHA.
[0094] Comparative Example 5
[0095] The components of the environmentally friendly and degradable rubber material of this comparative example are the same as those of Example 4, and specific reference is made to Example 4. The difference is that the accelerator of this comparative example 5 is directly mixed with 2-mercaptobenzothiazole and sodium isobutyl xanthate in a mass ratio of 11:50.
[0096] The mechanical properties, resilience, aging resistance, wear resistance, water resistance, chemical corrosion resistance and other properties of the environmentally friendly and degradable rubber materials obtained in the above Examples 1-4 and Comparative Examples 1-5 were tested, and the test results are shown in Table 1 below.
[0097] Tensile strength: tested according to the national standard GB / T528-2008.
[0098] Tear strength: tested according to the national standard GB / T529-2008.
[0099] Resilience: Tested according to the national standard GB / T1681-2009.
[0100] Aging resistance: Put the rubber material into a xenon lamp aging test chamber for aging test, and then conduct tensile strength test after aging for 500 hours;
[0101] Waterproofness: At room temperature, soak a 5cm×5cm×5mm rubber material sample in water for 24 hours, take it out, air-dry it for 12 hours, and then calculate the water absorption rate.
[0102] Chemical resistance:
[0103] The rubber material was placed in a 5% mass concentration sodium hydroxide solution for 24 hours, and then a tensile strength test was performed at a temperature of 35°C; the rubber material was placed in a 5% mass concentration sodium chloride saline solution for 24 hours, and then a tensile strength test was performed at a temperature of 35°C.
[0104] Table 1 Test results of rubber material properties obtained in the examples and comparative examples
[0105]
[0106]
[0107] According to the test results in Table 1 above, it can be seen that the environmentally friendly and degradable rubber material of the present invention has excellent mechanical strength, resilience, aging resistance, water resistance and chemical corrosion resistance, can replace chloroprene rubber, and is applied to deep-sea equipment (diving suits), and can also be applied to aerospace, wires and cables, automobiles, high-speed rail and other fields. The use of the benzothiazole-containing xanthate accelerator of the present invention and sulfur-HEA in combination greatly improves the mechanical strength, resilience, aging resistance, water resistance and other properties of the present invention.
[0108] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0109] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing an environmentally friendly and degradable rubber material, characterized in that: The specific steps include: S1. Putting natural rubber into an internal mixer for high temperature plasticization to obtain plasticized rubber; S2. The above-mentioned plasticized rubber is added to an internal mixer, and then reinforcing fillers, palm oil paste, antioxidants, and active agents are added in sequence. The first stage of plasticization is performed in the internal mixer at a temperature of ≤125°C for 30-60s to obtain the first stage of rubber mixing; S3. When the temperature of the first stage of rubber mixing reaches 125±2°C, add the required 1 / 3 mass fraction of rubber softening oil, zinc oxide, foaming agent, vulcanizing agent, and accelerator in turn, and perform the second stage of plasticizing in an internal mixer at a temperature of ≤115°C for 120-200s to obtain the second stage of rubber mixing; S4. When the temperature of the second stage of rubber mixing drops to 110±2°C, the remaining 2 / 3 mass fraction of rubber softening oil is added for the third stage of plasticizing. When the temperature of the third stage of plasticizing reaches 120±2°C, the third stage of rubber mixing is discharged from the internal mixer to obtain a rubber compound; S5. The rubber obtained in step S4 is placed in an open mill to cool down. When the temperature drops to 80±2°C, the rubber is thinly passed, packaged, and parked; S6. The parked rubber is placed in an open mill for heating, and then placed in an extruder for filtration and sheeting. The sheet is then placed in a flat vulcanizer for the first vulcanization and foaming at 140 ± 2 ° C; S7. After cleaning and trimming the vulcanized and foamed rubber material, vulcanization is performed for the second time to obtain the desired environmentally friendly and degradable rubber material.
2. The method for preparing an environmentally friendly and degradable rubber material according to claim 1, characterized in that: The environmentally friendly and degradable rubber material is made of the following raw materials in parts by weight: 100 parts of natural rubber, 22-27 parts of palm oil paste, 90-125 parts of reinforcing filler, 7.5-8.4 parts of foaming agent, 32-40 parts of rubber softening oil, 2.5-3.6 parts of vulcanizing agent, 2.0-4.0 parts of accelerator, 3.2-3.6 parts of zinc oxide, 5-7 parts of activator and 1.2-1.8 parts of antioxidant.
3. The method for preparing an environmentally friendly and degradable rubber material according to claim 2, characterized in that: The natural rubber is composed of No. 5 standard rubber and eucommia gum in a mass ratio of (7-10):
1.
4. The method for preparing an environmentally friendly and degradable rubber material according to claim 2, characterized in that: The reinforcing filler is composed of the following raw materials in parts by mass: 52-60 parts of kaolin, 35-45 parts of calcium carbonate and 12-20 parts of carbon black.
5. The method for preparing an environmentally friendly and degradable rubber material according to claim 2, characterized in that: The foaming agent is a composite foaming agent, which is composed of foaming agent AC, foaming agent OBSH and 5-aminotetrazole in a mass ratio of (2.6-3.0):1:0.
3.
6. The method for preparing an environmentally friendly and degradable rubber material according to claim 2, characterized in that: The vulcanizing agent is insoluble sulfur or sulfur-HEA.
7. The method for preparing an environmentally friendly and degradable rubber material according to claim 6, characterized in that: The preparation method of sulfur-HEA is as follows: sulfur and hydroxyethyl acrylate in a molar ratio of (2.2-2.6):1 are placed in a reactor, heated to 160-180° C. in a nitrogen environment, stirred for reaction for 2-4 hours, the product is taken out and quenched, and then placed in a 60-80° C. oven for 2-3 hours to obtain sulfur-HEA.
8. The method for preparing an environmentally friendly and degradable rubber material according to claim 2, characterized in that: The accelerator is a xanthate accelerator containing benzothiazole, and the preparation method of the xanthate accelerator containing benzothiazole specifically comprises the following steps: P1. Dopamine hydrochloride was dissolved in a Tris buffer with a pH value of 8.5 and ultrasonicated for 30 minutes, and then sodium isobutyl xanthate was added and ultrasonicated for 10 minutes, and then stirred at room temperature for 3-5 hours to obtain pretreated isobutyl xanthate; P2. Dissolve 2-mercaptobenzothiazole in anhydrous ethanol, then add the above-mentioned pretreated isobutyl xanthate, stir and react at 60-80°C for 3-6 hours. After the reaction is completed, filter, dry and crush to obtain the desired benzothiazole-containing xanthate accelerator.
9. The method for preparing an environmentally friendly and degradable rubber material according to claim 8, characterized in that: The amount of dopamine hydrochloride added is 6-9% of the mass of the sodium isobutyl xanthate; The added amount of the 2-mercaptobenzothiazole is 20-30% of the mass of the sodium isobutyl xanthate.
10. The method for preparing an environmentally friendly and degradable rubber material according to claim 2, characterized in that: The active agent is composed of oleylamine and zinc stearate in a mass ratio of 2:1; The antioxidant is any one or more of antioxidant MB, antioxidant MMB, antioxidant SP, antioxidant ZMMBI, and antioxidant NAPMA.
Citation Information
Patent Citations
High wear-resistant, high resilience, and environmentally friendly rubber materials and their preparation methods
CN111961265B
Preparation method of environment-friendly bio-based L-cysteine tire rubber
CN114716744A
Cited By
Low-density thermal insulation foam concrete and preparation method thereof
CN119638485A